Long Non-coding RNA AGAP2-AS1 Silencing Inhibits PDLIM5 Expression Impeding Prostate Cancer Progression via Up-Regulation of MicroRNA-195-5p - Xie, Pingbo; Liu, Mingsheng; Chen, Fen; Wu, Shaomei; Shao, Tao; Wang, Wei; Xu, Chenxiang; Zhou, Hongqing (Frontiers in Genetics, 2020)
Prostate cancer remains a significant cause of cancer-related deaths in male population. More recently, accumulating evidence continues to implicate long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in various types of cancers, including prostate cancer. The current study aimed to elucidate the role of lncRNA AGAP2-AS1/miR-195-5p/PDZ and LIM domain 5 (PDLIM5) in prostate cancer progression. Initially, microarray expression profiles were applied to screen differentially expressed lncRNAs/miRNAs/genes associated with prostate cancer. Dual-luciferase reporter and RNA pull-down/RIP assays were subsequently performed to explore the interactions among lncRNA AGAP2-AS1, miR-195-5p and PDLIM5, after which their expression was detected in cancer tissues and cells. Next, gain- and loss-of-function approaches were employed to elucidate the mechanism of lncRNA AGAP2-AS1/miR-195-5p/PDLIM5 in the processes of cell proliferation, migration and invasion as well as tumor growth. LncRNA AGAP2-AS1 was found to be highly expressed in prostate cancer. Silencing of lncRNA AGAP2-AS1 contributed to the suppression of proliferation, migration and invasion of cancer cells in vitro. Besides, lncRNA AGAP2-AS1 could bind to miR-195-5p which targeted PDLIM5 and subsequently downregulated its expression, ultimately impeding the progression of prostate cancer. Additionally, lncRNA AGAP2-AS1 inhibition led to an up-regulated expression of miR-195-5p and down-regulated PDLIM5 expression, resulting in delayed tumor growth in vivo. Taken together, the key findings of our study demonstrated that lncRNA AGAP2-AS1 silencing exerted suppressive effects on the development of prostate cancer via the miR-195-5p-dependent downregulation of PDLIM5. Our findings highlighted the potential of lncRNA AGAP2-AS1 as a promising novel molecular target for prostate cancer therapy.